PENGARUH PEMBERIAN BISPENOL-A (BPA) TERHADAP JUMLAH SPERMATOZOA PADA Rattus norvegicus GALUR WISTAR ALBINO - Tetra Anestasia Putri (LPPM UNIVERSITAS PERINTIS INDONESIA, 2019)
Bispenol-a (BPA) has an esterogen hormone activity while it enters the body, it can become endocrine disruptor. The objetive of this study was to purpose to prove that bispenol a can decrease spermatozoa cell count in male wistar albino strain rats (rattus novergicus).This research is an experimental design with post-only control group by using 20 male wistar albino strain rats (rattus Novergicus). Those sample aged 2-3 months which divided into four groups for 5 rats each. Control group (K) without bispenol-a adduction. The first (P1), second (P2), and third (P3) group treatment was given with BPA in 51 days for 0.45, 0.9 and 1.8 mg/body weight(kgs)/day for a 51-day. After 51-day treatment.This research showed that mean value of testosterone hormone for control group was 7.78 ng/lts. P1 group, P2 and P3 groups showed 6.19, 5.23 and 4.02 ng/lt.the count of spermatozoa has mean value for control group was 39,1 while first group (P1) was 30.2 . In second (P2) and third (P3) treatment group were 21,1 and 19.7. Data analysis showed mice spermatozoa cell count had p <0.05, which means that there is significance differentiation between control and treatment groups.It can be concluded that there is an effect of bisphenol a adduction on male Rattus novergicus wistar albino strain spermatozoa cell count.